Critical Review on cathode–electrolyte Interphase Toward High-Voltage Cathodes for Li-Ion Batteries - Xu, Jijian (Nano-Micro Letters, 2022)
The thermal stability window of current commercial carbonate-based electrolytes is no longer sufficient to meet the ever-increasing cathode working voltage requirements of high energy density lithium-ion batteries. It is crucial to construct a robust cathode–electrolyte interphase (CEI) for high-voltage cathode electrodes to separate the electrolytes from the active cathode materials and thereby suppress the side reactions. Herein, this review presents a brief historic evolution of the mechanism of CEI formation and compositions, the state-of-art characterizations and modeling associated with CEI, and how to construct robust CEI from a practical electrolyte design perspective. The focus on electrolyte design is categorized into three parts: CEI-forming additives, anti-oxidation solvents, and lithium salts. Moreover, practical considerations for electrolyte design applications are proposed. This review will shed light on the future electrolyte design which enables aggressive high-voltage cathodes. Highlights: 1 A critical assessment of cathode–electrolyte interphase (CEI) for high-voltage cathode electrodes in Li-ion cells. 2 Fundamental understanding of why interfacial interphase is important to electrochemical performance and further elaboration on how to design robust CEI interphase. 3 Emerging theoretical simulations and advanced in situ characterizations helps to unveil the mystery of CEI are summarized.